New wild Brassica oleracea L. germplasm at its western distribution limit in the Iberian Peninsula - Fagúndez, Jaime; Cartea, María Elena; Lema, Margarita (Lazaroa, 2015)
An exploration and collection mission for wild Brassica oleracea populations was carried out in spring and summer of 2013. The aim of this collection was to expand the number of accessions of wild Brassica oleracea available for basic and applied research in plant breeding. In this paper we report a new accession of wild Brassica oleracea in an unexplored coastal area of Galicia, NW Iberian Peninsula. Details of population ecology and vegetation, soil, climate and geographic data were recorded for this population. The “Endangered” threat category for the region is proposed, and actions for in situ and ex situ conservation are proposed. Seeds will be added to the germplasm collections of University of Santiago de Compostela and Misión Biológica de Galicia (CSIC) for further research on diverse aspects of the dynamics and ecophysiology of the population along with characterization and evaluation of useful traits.